All-solid-state Li-metal batteries: role of blending PTFE with PEO and LiTFSI salt as a composite electrolyte with enhanced thermal stability. Issue 5 (25th February 2020) - Jokhakar, Deep A.; Puthusseri, Dhanya; Manikandan, Palanisamy; Li, Zheng; Moon, Jooho; Weng, Hsin-Jan; Pol, Vilas G.
Abstract : Enhancing the ionic conductivity and thermal stability of solid electrolytes is crucial for the development of all-solid-state batteries. Abstract : Enhancing the ionic conductivity and the thermal stability of solid electrolytes is crucial for the development of all-solid-state batteries. Here, we report polytetrafluoroethylene (PTFE) as an additive to improve the ionic conductivity and thermal stability of polyethylene oxide (PEO) based electrolytes. Electrochemical Impedance Spectroscopy (EIS) measurements for composite electrolytes with varying ratios of PEO and PTFE confirm the enhancement in the ionic conductivity at both room temperature and 60 °C. From the EIS measurements of electrolytes at room temperature, PEO100 showed the lowest ion conductivity (2.25 × 10 −8 S cm −1 ), while electrolytes with added PTFE showed a higher ion conductivity (6.62 × 10 −8 S cm −1 ). The charge–discharge measurement confirms that adding PTFE improved the capacity from 139 mA h g −1 to 163 mA h g −1 with cycling stability. Furthermore, the thermal stability of PTFE blended PEO composite electrolyte is enhanced, resulting in lower heat liberation by a factor of two compared with PEO electrolyte. Our results show that PTFE–PEO composite has the potential to be used as a solid electrolyte in lithium metal batteries.